Membrane Cholesterol Is Crucial for Clostridium difficile Surface Layer Protein Binding and Triggering Inflammasome Activation - Chen, Yu; Huang, Kai; Chen, Liang-Kuei; Wu, Hui-Yu; Hsu, Chih-Yu; Tsai, Yau-Sheng; Ko, Wen-Chien; Tsai, Pei-Jane (Frontiers in Immunology, 2020)
Clostridium difficile, an obligate anaerobic gram-positive bacillus, generates spores and is commonly found colonizing the human gut. Patients with C. difficile infection (CDI) often exhibit clinical manifestations of pseudomembranous colitis or antibiotic-associated diarrhea. Surface layer proteins (SLPs) are the most abundant proteins in the C. difficile cell wall, suggesting that they might involve in immune recognition. Our previous results demonstrated that C. difficile triggers inflammasome activation. Here, we found SLPs as well as C. difficile induced inflammasome activation, and in a dose-dependent manner. In addition, the cholesterol-rich microdomains on the cell membrane (also referred to as lipid rafts) are thought to be crucial for bacterial adhesion and signal transduction. We demonstrated that lipid rafts participated in C. difficile SLPs binding to the cell membrane. Fluorescence microscopy showed that membrane cholesterol depletion by methyl-β-cyclodextrin (MβCD) reduced the association of SLPs with the cell surface. The coalescence of SLPs in the cholesterol-rich microdomains was confirmed in C. difficile-infected cells. Furthermore, the inflammasome activations induced by SLPs or C. difficile were abrogated by MβCD. Our results demonstrate that SLPs recruit the lipid rafts, which may be a key step for C. difficile colonization and inducing inflammasome activation.